Constraints and contributors in advancing Black women academic researchers at a university in South Africa - Schultz, C.; Rankhumise, E. (South African Journal of Higher Education, 2023)
This article draws from a project that was conducted at a South African university to investigate the advancement of Black women academic researchers. A qualitative research method was used to obtain rich data from Black women academics. Thematic analysis was used to analyse the data. Findings from the study suggest that the constraints in advancing Black women academics were: research was not a priority; problems with work-life balance; research challenges; a male-dominated environment; time constraints; lack of support; and funding. The contributors in advancing Black women academic researchers were perseverance, collaboration, co-supervision, motivation, mentorship and support, including institutional support. There ought to be a deeper inquiry into how best to ensure the advancement of Black women academics at universities in South Africa.